2019
DOI: 10.1007/s11837-019-03960-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of Platinum Loss in WEEE Smelting

Abstract: In spite of significant economic value, the solubilities of the platinum group and precious metals in metallurgical copper smelting slags are not well known. Recent experimental information on iron-free and low-iron silicate melts indicates that the chemical solubility of platinum is very low,< 1 ppmw (part per million weight). In this study, the concentration of platinum in alumina spinel-saturated iron silicate slags in equilibrium with a solid ironplatinum alloy was measured as a function of oxygen partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Those results are opposite to the present decreasing trends but agree well with the observation by Shuva et al [64] Klemettinen et al [65] reported that the platinum solubility in alumina spinel-saturated FeO x -SiO 2 -Al 2 O 3 slag equilibrated with pure platinum increased from around 15 to 80 ppbw when the P O 2 increased from 10 À10 to 10 À5 atm. The solubility data reported by study; open symbols-our previous study [25] Klemettinen et al [65] were extremely low, even at the highest P O 2 of copper-making conditions, around 10 À5 atm. Murata and Yamaguchi [66] investigated the recovery of platinum and palladium from an Al 2 O 3 -CaO-SiO 2 slag using Cu or Cu 2 O.…”
Section: Concentrations Of Precious Metals In Slagssupporting
confidence: 91%
See 1 more Smart Citation
“…Those results are opposite to the present decreasing trends but agree well with the observation by Shuva et al [64] Klemettinen et al [65] reported that the platinum solubility in alumina spinel-saturated FeO x -SiO 2 -Al 2 O 3 slag equilibrated with pure platinum increased from around 15 to 80 ppbw when the P O 2 increased from 10 À10 to 10 À5 atm. The solubility data reported by study; open symbols-our previous study [25] Klemettinen et al [65] were extremely low, even at the highest P O 2 of copper-making conditions, around 10 À5 atm. Murata and Yamaguchi [66] investigated the recovery of platinum and palladium from an Al 2 O 3 -CaO-SiO 2 slag using Cu or Cu 2 O.…”
Section: Concentrations Of Precious Metals In Slagssupporting
confidence: 91%
“…To ensure the achievement of equilibrium and improve the accuracy of the experimentally measured data, a method employing high-temperature isothermal equilibration followed by rapid quenching and direct phase analysis [32,33] was developed and has been widely used for investigating matte-slag equilibria. [34][35][36][37][38][39][40][41][42][43][44] Recently, Electron Probe X-ray Microanalysis (EPMA) and Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS) analytical techniques were successfully applied to measure the concentrations of precious metals in matte/metal and slag, [21][22][23][24][25][26][27][28][29][30][31] leading to increased accuracy and reliability of the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was not conducted due to the high risk of the inclusion of entrained metal droplets in the analyzed slag volume, which would have significantly distorted the concentration values obtained for minor/trace elements in the slag. The benefits of direct phase analysis methods over manual phase separation followed by chemical analyses for trace element quantifications have been discussed in the literature [40,41].…”
Section: Methodsmentioning
confidence: 99%
“…The details of the experimental furnace and the gas train have been described earlier. 16,17 This study continues the PGM solubility studies in a similar Fe alloy-slag system with the same experimental arrangement and procedure as previously published for platinum. 16 The sample and an alumina crucible as the sample holder in the hot zone of the experimental furnace are shown in Fig.…”
Section: Methodsmentioning
confidence: 80%